2019
DOI: 10.46624/ajphr.2019.v7.i2.001
|View full text |Cite
|
Sign up to set email alerts
|

Irrational Use of Drugs – A Review

Abstract: Everybody wants to get success in their life but on the cost of their health. Due to that the chances of irrationality of drugs increase in which self-medication is one of the major cause. The basic principle for the rational use of drug is better supply of drugs, better prescribing and lower costs for health care. When the basic principle of rational use of drugs is not fulfill it leads to irrationality which further leads to adverse effects and toxicity. There are number of factors which contributes to irrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Study findings showed that some sociocultural factors such as public limited knowledge, habitual use of antibiotics, and patients' insistence on antibiotic prescription contributed to IRAP. Medication prescription is a complex process affected by sociocultural factors [29] such as patients' educational level, expectations, and previous experiences of medication use [41]. The physicians' paternalistic approach in healthcare systems in Iran, their ineffective communication with pharmacologists and other healthcare providers, and their tendency towards satisfying their patients are among the most important factors contributing to IRAP [42].…”
Section: Discussionmentioning
confidence: 99%
“…Study findings showed that some sociocultural factors such as public limited knowledge, habitual use of antibiotics, and patients' insistence on antibiotic prescription contributed to IRAP. Medication prescription is a complex process affected by sociocultural factors [29] such as patients' educational level, expectations, and previous experiences of medication use [41]. The physicians' paternalistic approach in healthcare systems in Iran, their ineffective communication with pharmacologists and other healthcare providers, and their tendency towards satisfying their patients are among the most important factors contributing to IRAP [42].…”
Section: Discussionmentioning
confidence: 99%